Factors Associated with the Role of Nurses in Performing Airway Management, Breathing and Circulation Management for Head Injury Patients in the Emergency Room of Ulin Hospital Banjarmasin - Rifki Fatimah; Novia Heriani (UrbanGreen, 2019)
Head injuries occupy the highest levels of morbidity and mortality, therefore it requires better understanding and management, especially regarding treatment. One of the most successful treatment for head injuries is structured first aid management, namely Airway, Breathing and Circulation. To find out factors related to the role of nurses in carrying out ABC management actions in head injury patients at the emergency department of Ulin Hospital Banjarmasin. This type of quantitative research with observational methods, using the Cross Sectional Study design, the sample is an executive nurse who provides ABC management to 34 people with head injury patients, taken by purposive sampling method, the data were analyzed using the Spearman Rank Test. The study found that there was statistical significance between ABC management with education levels (p = 0.004),length of employment (p = 0.000), emergency training (p = 0.000) and emergency facilities (p = 0.000).